By Kelman Out of Pessoa - Nufer, Doug (punctum books, 2023)
In 2002, Doug Nufer wrote a story narrated by a tout, who proposed a novel way to beat the races. It was so absurd and ludicrous it gave him an idea. So Nufer went to Emerald Downs, home of thoroughbred racing in the Northwest. There, he split himself into three characters modeled on the heteronyms of Fernando Pessoa. Using a money management plan from a James Kelman short story, Nufer gave these characters money and set them free to gamble. He returned to the track every week for a full season, and his characters/heteronyms continued to bet, with real money and in the name of art. At the end of the season, he had pages of data in the form of a wagering diary, the outcome of a literary experiment that formed the basis of a literal experimental novel.